Popisho - Ross, Leone, 1969- (Farrar, Straus and Giroux, 2021)
"Somewhere far away - or maybe right nearby - lies an archipelago called Popisho. A place of stunning beauty and incorrigible mischief, destiny and mystery, it is also a place in need of change. Xavier Redchoose is the macaenus of his generation, anointed by the gods to make each resident one perfect meal when the time is right. Anise, his long-lost love, is on a march toward reckoning with her healing powers. The governor's daughter, Sontiene, still hasn't come into her cors, but her corrupt father is demanding the macaenus make a feast for her wedding. Meanwhile, graffiti messages from an unknown source are asking hard questions. A storm is brewing. Before it comes, before the end of the day, this wildly imaginative narrative will take us across the islands, through their history, and into the lives of unforgettable characters."Publisher.